2017
DOI: 10.1097/tp.0000000000001119
|View full text |Cite
|
Sign up to set email alerts
|

Overall Graft Loss Versus Death-Censored Graft Loss

Abstract: Background Black kidney transplant recipients experience disproportionately high rates of graft loss. This disparity has persisted for 40 years and improvements may be impeded based on the current public reporting of overall graft loss by U.S. regulatory organizations for transplantation. Methods Longitudinal cohort study of kidney transplant recipients using a dataset created by linking Veterans Affairs and U.S. Renal Data System information, including 4,918 veterans transplanted between Jan 2001 and Dec 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Our results are consistent with prior findings that link the risk of graft rejection or failure to Black race, male gender, age, hypertension, and glomerulonephritis [16,[19][20][21][22]. A retrospective, cross-sectional study that used HCUP-NIS 1995-2005 discharge data found that independent predictors of complications following renal transplant included older age, male gender, and CCI ≥ 1 [22]. Our findings are consistent with the results of previous studies that highlight racial disparities in renal transplant outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with prior findings that link the risk of graft rejection or failure to Black race, male gender, age, hypertension, and glomerulonephritis [16,[19][20][21][22]. A retrospective, cross-sectional study that used HCUP-NIS 1995-2005 discharge data found that independent predictors of complications following renal transplant included older age, male gender, and CCI ≥ 1 [22]. Our findings are consistent with the results of previous studies that highlight racial disparities in renal transplant outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with the results of previous studies that highlight racial disparities in renal transplant outcomes. For example, in their longitudinal, cohort study of 4,918 renal transplant recipients (33% were non-Hispanic Black recipients), Taber et al [22] found that non-Hispanic Blacks were significantly more likely to experience graft loss; others have noted that Blacks have worse outcomes in sepsis, likely due to a multitude of factors [23,24]. How these factors intersect in renal transplant patients with sepsis is not understood and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We validated data elements by comparing them between the two databases for accuracy and were able to include the largest number of covariates ever reported in a transplant racial disparities analysis. 40 In addition, retrospectively accurately assessing control of CVD risk factors is a difficult endeavor, and using means during the entire follow up may not truly capture the time dependency of this exposure. However, using the means does allow for a more straightforward analysis and presentation of the data.…”
Section: Discussionmentioning
confidence: 99%
“…1720 There have been numerous studies elucidating the explanatory factors associated with this disparity, including biologic differences (immunologic risk and gene polymorphisms) and socioeconomic disadvantages. 2126 AAs are substantially more likely to express the CYP 3A5 *1 polymorphism, which is linked to increased tacrolimus clearance and variability.…”
Section: Introductionmentioning
confidence: 99%